EFFECT OF TEMPERATUiRE ON RESPIRATION OF LABEO FIMBRIATUS (BLOCH) - Kasim, H Mohamad (Indian Journal of Fisheries, 2011)
Labeo fimbriatus (Bloch) was tested at non-lethal temperatures to measureits oxygen uptake both in oxygen dependant and independant zones. The metabolicrate was almost uniform in oxygen independant zone, in oxygen dependant zonereduced drastically and then oxygen level becomes lethal. This species regulatedthe oxygen consumption at lower rate at extreme high and low temperatures thanat intermediary optimum temperatures. The lethal oxygen level was much higherat low temperatures, whereas it was the lowest at optimum temperature. The highestlethal oxygen level at low temperature is attributed to the inhibition in oxygenuptake. Cold-acclimated fish consumed more oxygen than the warm-acclimatedfish. The time to death was the highest at low temperature